The Correlation between Junk Food Consumptive Behavior and the Nutritional Statuses of Primary School Learners - Rachma Dewi, Ervi; David Laksamana Caesar; Nadia Siti Nurfatma (Universitas STRADA Indonesia, 2023)
The nutritional status of elementary school children is very important to improve because it will determine the quality of life of children and also affect the nation's future development process. Abnormal nutrition in children will inhibit growth, lower intelligence levels, and weaken the immune system. Most of the behavior of millennial generation children is the habit of eating unbalanced food such as fast food (junk food) which will have an impact on children's nutritional status. This study head to determine the correlation between junk food consumption behavior and nutritional status at SDN Pati Kidul 05. Method this research is Observational analytics with cross-sectional research design, and quantitative research type. The population used was all students in grades IV and V with a sample of 50 students taken using a saturated sampling technique. The research instrument was a questionnaire of knowledge, attitudes, practices, body scales, and microtoise. The statistical analysis used is the chi-square test. The study showed that there was no significant correlation between knowledge and the nutritional status of children at SDN Pati Kidul 05 using the chi-square test to obtain a p-value = 0.459. There was no significant correlation between attitude and nutritional status of children at SDN Pati Kidul 05 using the chi-square test to obtain a p-value = 0.375. There is no significant correlation between practice and the nutritional status of children at SDN Pati Kidul 05 using the chi-square test to obtain a p-value = 0.706. The results of the study show that there is no significant correlation between knowledge, attitude, and practice with the nutritional status of children.